The Implementation Of Sak Emkm In The Preparation Of Financial Statements At Rumah Barbershop Msme - Azwan Bastian; Muhammad Ihsan Rangkuti; Handriyani Dwilita (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to apply the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the preparation of financial statements for Rumah Barbershop MSMEs in South Binjai. Currently, the financial recording practices are still basic and limited to cash inflows and outflows, which prevents business owners from accurately identifying their financial position and profit or loss. This research employs a qualitative method with a descriptive approach through observation, interviews, and documentation. The findings indicate that Rumah Barbershop MSMEs have not implemented SAK EMKM due to limited accounting knowledge and resource constraints. Through transaction data analysis, this study prepares financial position statements, income statements, and notes to the financial statements in accordance with SAK EMKM. The implementation of this standard is expected to improve the quality of financial information, support more informed decision-making, and assist MSMEs in managing their businesses more effectively and sustainably.